Phenolic profile of different solvent extracts of Reseda alba L. and evaluation of anti-quorum sensing, antioxidant, and enzyme inhibition activities - Nacer, Mohammed; Kalla, Ali; Tamfu, Alfred Ngenge; Boudiba, Sameh; Hanini, Karima; Hioun, Soraya; Messaoudi, Mohammed; Atoki, Ayomide Victor; Kucukaydin, Selcuk; Latifa, Khattabi; Ceylan, Ozgur; Boudiba, Louiza (Frontiers in Nutrition, 2025)
BackgroundReseda alba (white mignonette) is a wild, edible, and medicinal plant native to the Mediterranean region, with limited studies on its chemical composition and bioactivities.MethodsThe phenolic profile and bioassays of antioxidant, anti-swarming, quorum sensing (QS), and enzyme inhibitory activities of different solvent extracts of R. alba are investigated using high-performance liquid chromatography with diode-array detection (HPLC-DAD).ResultsRosmarinic acid was identified as the predominant phenolic compound in the ethyl acetate extract (197.5 ± 0.25 μg/g) and n-butanol extract (205.4 ± 0.47 μg/g). Minimal inhibitory concentrations (MICs) ranged from 0.3125 to 2.5 mg/mL against Chromobacterium violaceum and Pseudomonas aeruginosa PA01. These extracts demonstrated significant inhibition of quorum sensing and swarming motility against C. violaceum and P. aeruginosa PA01 at MIC and sub-MIC. Extracts exhibited inhibition of enzymes, especially cholinesterases implicated in neurodegenerative diseases. The extracts demonstrated antioxidant activity, as determined through six assays, with the dichloromethane extract (DCME) exhibiting higher antioxidant activity compared to the standards α-tocopherol and ascorbic acid in the ferric-reducing antioxidant power (FRAP) assay.ConclusionThe results demonstrate that R. alba extracts (RAEs) possess significant inhibitory effects on enzymes implicated in neurodegenerative disorders, such as Alzheimer’s disease, particularly through butyrylcholinesterase inhibition. Additionally, the extracts show promising anti-quorum sensing and anti-swarming activities, which could reduce microbial virulence and biofilm formation, suggesting potential as alternative antimicrobial agents. The moderate antioxidant activity further supports its therapeutic potential. Overall, R. alba could be developed as a natural source for managing enzyme-related diseases and controlling bacterial infections by targeting microbial communication mechanisms.